Capillary refill time in sepsis: A useful and easily accessible tool for evaluating perfusion in children - Lamprea, Shirley; Fernández-Sarmiento, Jaime; Barrera, Sofía; Mora, Alicia; Fernández-Sarta, Juan Pablo; Acevedo, Lorena (Frontiers in Pediatrics, 2022)
Abstract The international sepsis guidelines emphasize the importance of early identification along with the combined administration of fluids, antibiotics and vasopressors as essential steps in the treatment of septic shock in childhood. However, despite these recommendations, septic shock mortality continues to be very high, especially in countries with limited resources. Cardiovascular involvement is common and, in most cases, determines the outcomes. Early recognition of hemodynamic dysfunction, both in the macro and microcirculation, can help improve outcomes. Capillary refill time (CRT) is a useful, available and easily accessible tool at all levels of care. It is a clinical sign of capillary vasoconstriction due to an excessive sympathetic response which seeks to improve blood redistribution from the micro- to the macrocirculation. An important reason for functionally evaluating the microcirculation is that, in septic shock, the correction of macrocirculation variables is assumed to result in improved tissue perfusion. This has been termed “hemodynamic coherence.” However, this coherence often does not occur in advanced stages of the disease. Capillary refill time is useful in guiding fluid resuscitation and identifying more seriously affected sepsis patients. Several factors can affect its measurement, which should preferably be standardized and performed on the upper extremities. In this review, we seek to clarify a few common questions regarding CRT and guide its correct use in patients with sepsis.